ANALYSIS OF THE USE OF PERSONAL PROTECTIVE EQUIPMENT (PPE) AND SAFETY BEHAVIOR OF WORK ACCIDENTS IN TRADITIONAL SANDMINERS IN KALI BLADAK VILLAGE, BLITAR DISTRICT - Kusuma, Hafiz; Novita Ana Anggraeni (Journal of Global Research in Public Health, 2020)
Occupational accidents often occur in workers, especially traditional workers who have not implemented the concept of occupational health and safety. This is evidenced by the incidence of work accidents that claimed lives in the traditional sand mining area of ​​Kali Bladak village. The purpose of this study was to analyze the effect of the use of personal protective equipment (PPE) and work safety behavior on the incidence of work accidents in traditional sand miners in Kali Bladak Village, Blitar Regency. The design of this research is an observational quantitative study with a cross sectional approach with the focus of the research being directed to analyze the effect of the use of personal protective equipment (PPE) and work safety behavior on the incidence of work accidents in traditional sand miners in Kali Bladak Village, Blitar Regency with a population of 46 respondents and Samples of 41 respondents were taken using the Simple Random Sampling technique. The findings showed that most of the respondents used complete personal protective equipment as many as 22 respondents (53.7%). Nearly half of the respondents have adequate occupational safety behavior The findings showed that most of the respondents used complete personal protective equipment as many as 22 respondents (53.7%). Nearly half of the respondents have adequate occupational safety behavior The findings showed that most of the respondents used complete personal protective equipment as many as 22 respondents (53.7%). Nearly half of the respondents have adequate occupational safety behavior as many as 17 respondents (41.5%). Most of the respondents had experienced work accidents as many as 21 respondents (51.2%). The results of the study using the Logistic Regression Test showed that the p-value was 0.004 and 0.002 <0.05, so H0 was rejected and H1 was accepted, so it was concluded that there was an effect of the use of personal protective equipment (PPE) and work safety behavior on the incidence of work accidents in traditional sand miners in Kali Bladak Village, Blitar Regency. When working with sand miners that have a high risk of disability while working, they must use complete personal protective equipment (PPE) and behave in a safe manner so that work safety and security can be increased.